Understanding Pro-environmental Behaviour on Green Tourism: Impacted by Destination Social Responsibilty and Green Trust as an Intervening Variabel - Nihayatu Aslamatis Solekah; Mardiana; Muhammad Fatkhur Rozi; Hary Saputro Kurniawan (Journal of Social Transformation and Regional Development, 2024)
Tourist destinations have an essential role in the form of social responsibility to create environmentally friendly behavior for tourists who visit them. This research aims to examine the influence of destination social responsibility and green trust on tourists’ pro-environment in green tourism. This research also identifies the mediating role of green trust between destination social responsibility and tourists’ pro-environment in green tourism. The study used a purposive sampling of 200 tourists who visited green tourism destinations in Malang, East Java, Indonesia. Data analysis checks a statistical model using the SmartPLS 4 program for the structural-partial least squares (SEM-PLS. The results show that destination social responsibility and green continue to influence tourists’ pro-environment, and destination social responsibility influences green trust. Green trust mediates the influence of Destination social responsibility on tourists’ pro-environment. The results of this research provide implications for the importance of DSR’s role in increasing tourists’ green trust perceptions, which will lead to the formation of pro-environment behavior in the green tourism destinations they visit.